2006
DOI: 10.1677/joe.1.06869
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of the GH/IGF system genes during refeeding in rainbow trout (Oncorhynchus mykiss)

Abstract: The GH/IGF system is a complex regulation network strongly dependent on nutrient availability. While the effect of starvation on the GH/IGF system has been extensively studied, the time course of events leading to the restoration of GH/IGF system activity after starvation is largely unknown. We, therefore, measured the plasma levels of GH, IGF-I and IGF-II and the expression of the GH/IGF system in liver and muscle. Starvation increased the plasma GH level and 1 day of refeeding completely restored it (1$10G0$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
125
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(144 citation statements)
references
References 50 publications
18
125
1
Order By: Relevance
“…These results are in concordance with the studies in goldfish, flounder, rainbow trout and salmons (Canosa et al, 2005;Fuentes et al, 2012;Gabillard et al, 2006;Pierce et al, 2005;Shimizu et al, 2009). Next, we observed high expression levels of serum GH in both fasted and fed TG common carp, while there is no significant difference between them ( Fig.…”
Section: Gh and Hypothalamic Feeding Regulationsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in concordance with the studies in goldfish, flounder, rainbow trout and salmons (Canosa et al, 2005;Fuentes et al, 2012;Gabillard et al, 2006;Pierce et al, 2005;Shimizu et al, 2009). Next, we observed high expression levels of serum GH in both fasted and fed TG common carp, while there is no significant difference between them ( Fig.…”
Section: Gh and Hypothalamic Feeding Regulationsupporting
confidence: 92%
“…Furthermore, changes in GH levels are tightly coupled to nutritional status (Canosa et al, 2007). For example, reduced food intake or starvation causes GH to rise, while GH returns to baseline after resumed feeding (Gabillard et al, 2006;Pierce et al, 2005;Shimizu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has also been shown that SOCS proteins interact with GH receptor signalling (Wang et al, 2011). Fish growth is a complex function mostly regulated by the growth hormone (GH)/insulin-like growth factor (IGF) system (Gabillard et al, 2006). Over-expression of SOCS-2 has been shown to interfere with the JAK2-STAT5b pathway and inhibit growth hormone signalling (Croker et al, 2008).…”
Section: Socs Modulationmentioning
confidence: 99%
“…For example, in both rainbow trout and gilthead sea bream, fasting increased plasma GH levels and decreased tissue expression and plasma levels of IGFs and upregulated IGF-I binding (Gabillard et al, 2006a;Montserrat et al, 2007a and. In trout, fasting followed by refeeding causes a switch to fast growth and involves the local upregulation of several components of the IGF system (Gabillard et al, 2006a).…”
Section: Consequences Of Maternal Nutritionmentioning
confidence: 99%
“…For example, in both rainbow trout and gilthead sea bream, fasting increased plasma GH levels and decreased tissue expression and plasma levels of IGFs and upregulated IGF-I binding (Gabillard et al, 2006a;Montserrat et al, 2007a and. In trout, fasting followed by refeeding causes a switch to fast growth and involves the local upregulation of several components of the IGF system (Gabillard et al, 2006a). Moreover, IGF-I stimulates cell proliferation in both rainbow trout (Castillo et al, 2004 and2006) and gilthead sea bream (Montserrat et al, 2007c) muscle cells in vitro and IGF-II has both mitogenic and metabolic effects in trout muscle cell cultures (Codina et al, 2008).…”
Section: Consequences Of Maternal Nutritionmentioning
confidence: 99%